Honor Killing di Timur Tengah: Konstruksi dan Respons Hukum Pidana di Yordania, Lebanon, dan Palestina - Zul Khaidir Kadir (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This article examines honor killing in the Middle East as a form of gender-based killing rooted in the close relationship between family honor, sexual morality, and patriarchal control over women. Honor killing cannot be reduced to ordinary domestic homicide, because it operates through the belief that a woman’s body, conduct, and life choices are directly tied to the collective reputation of her family. The analysis is structured around three objectives. First, it explains how honor and family morality shape gender control. Second, it identifies the patterns, triggers, and forms of honor killing. Third, it analyzes legal responses and prevention strategies through a comparison of Jordan, Lebanon, and Palestine. This study employs a normative legal method, combining statutory, case-based, and comparative approaches. Its primary legal materials include the relevant criminal provisions in the three jurisdictions, notably Articles 340, 98, and 99 of the Jordanian Penal Code, Article 562 of the Lebanese Penal Code before its repeal in 2011, and Palestine’s Decree-Law No. 7 of 2011. The findings show that honor killing is not triggered only by proven sexual misconduct. In many cases, violence emerges from allegations, suspicion, rumor, refusal of family-arranged choices, or conduct by women considered damaging to the family’s collective reputation. Women remain the principal victims, while perpetrators are most often close family members. Legal reforms in the three jurisdictions mark an important normative shift, yet their practical effect remains constrained by general mitigating excuses, institutional bias, family pressure, and weak victim protection. These findings show that honor killing persists because social legitimacy and legal leniency continue to reinforce one another. Addressing this crime therefore requires more than formal amendment of criminal provisions. It also demands stricter sentencing policy, rights-based victim protection, and sustained transformation of the social norms that continue to legitimize killing in the name of honor.